(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Human lifestyle development is related to different physiological or social lifestyle disorders, and hyperlipidemia is one of them which requires rapid attention. Present study is carried out to fortify a traditional Assamese breakfast item Sandoh guri (roasted parboiled rice powder) with green gram Dal, Arjuna, cinnamon and fenugreek to put in hypolipidemic property into it. All ingredients are washed, sundried, roasted and powdered. Powdered parboiled rice, green gram Dal, Arjuna, cinnamon and fenugreek are mixed together in proportion of 70:30:2:2:2. The proximate composition of the mix and values of a few micronutrients in the mix are found out through standard biochemical methods and calculations using standard nutritive value of ingredients present. Per 100 grams of the mix contain 74.75 g carbohydrates, 12.92 g protein, 1.07 g fat (0.45 g saturated, 0.4 g monounsaturated and 0.51 g polyunsaturated fatty acids) and 7.13 g dietary fibre. Main nutrients with antioxidant properties in the mix are vitamin A (29.8 IU), vitamin E (0.57 mg), vitamin C (0.16 mg), selenium (11.2 mcg), copper (193.4 mcg), zinc (529.2 mcg), iron (2531 mcg) and manganese (810.7 mcg) .The nutritive value analysis verifies that this developed health mix is a much better breakfast alternative for a hyperlipidemic person compared to any other commonly used breakfast food items.